Understanding silicate hydration from quantitative analyses of hydrating tricalcium silicates - Elizaveta Pustovgar (Nature Portfolio, 2016)
Despite its importance to the cement industry, tricalcium silicate hydration, with its sequence of induction, acceleration and deceleration steps, still hosts many open questions. Here, 29Si nuclear magnetic resonance provides new information on the silicate polymerization mechanism and its kinetics.